The Effect of Tax Knowledge, Tax Sanctions and Fiscal Services on Taxpayer Compliance (Empirical Study on Corporate Taxpayers at KPP Pratama Purwokerto) - Noor Salim Salim; Asriani Yuli Saputri (Accounting Study Program, Faculty of Economics and Business, 2022)
The purpose of this study is to determine the knowledge of taxation, tax sanctions, and tax authorities on taxpayer compliance in carrying out tax obligations, namely calculating, paying and reporting taxes owed. The population in this study were the corporate taxpayers at KPP Pratama Purwokerto. The sample is determined by random sampling of 100 respondents. The method used to analyze the data is regression analysis. The method of collecting data using a questionnaire. The questionnaire was tested for validity and reliability before collecting research data. The analysis technique in this study uses the classical assumption test and multiple linear regression analysis. The results of this study indicate that knowledge of taxation has no effect on taxpayer compliance, while tax sanctions and tax administration services have a positive effect on taxpayer compliance.